2020
DOI: 10.1002/saj2.20104
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of corn stover removal on carbon dioxide and nitrous oxide emissions

Abstract: Harvesting corn (Zea mays L.) stover for production of biofuels, industrial sugars, bioproducts, and livestock bedding is increasing rapidly, but little is known of the impacts of stover removal on soil-borne greenhouse gas (GHG) emissions. This study evaluated the impacts of removing surface corn stover (0, 25, 50, 75, 100 wt. % removal) on carbon dioxide (CO 2) and nitrous oxide (N 2 O) emissions from a sandy loam soil cropped to monoculture corn using conventional moldboard plow tillage (CT) and no-tillage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Coefficients with values > |0.3| and that are statistically significant are shown in bold front. The apparent immobilization of IN when high crop residues are present compared to crop removal were also observed in a stover removal field study at 5 residue removal rates (Drury et al, 2020). They found greater nitrate exposure when crop residues were removed which resulted in greater N 2 O emissions compared to the no residue removal treatment.…”
Section: Soil Health Indicatorsmentioning
confidence: 68%
“…Coefficients with values > |0.3| and that are statistically significant are shown in bold front. The apparent immobilization of IN when high crop residues are present compared to crop removal were also observed in a stover removal field study at 5 residue removal rates (Drury et al, 2020). They found greater nitrate exposure when crop residues were removed which resulted in greater N 2 O emissions compared to the no residue removal treatment.…”
Section: Soil Health Indicatorsmentioning
confidence: 68%
“…% stover removal based on the annual stover yield from CT at the 100% removal rate. Basing removal rates on annual stover yield from one treatment (in this case, CT at 100% removal) accounts for year‐to‐year variation in stover yields (see Drury et al., 2020). Although no stover was re‐applied to the 100% removal treatments, a small amount remained on these plots because of stalks and residues that were not picked up by the baler.…”
Section: Methodsmentioning
confidence: 99%
“…The stover was incorporated into CT soils by the annual fall plowing operation, but left undisturbed on the surface of NT soils. Further detail on experimental design and field methods can be found in Drury et al (2020).…”
Section: Experimental Design and Agronomymentioning
confidence: 99%
“…Air, Soil and Water Research Drury et al (2021) reported that reducing residue rate increased the cumulative emissions of N 2 O under both conventional and no-tillage systems and the highest emissions were related to the complete removal of residue. They attributed the reduction of N 2 O emissions in residue conservation treatments to N immobilization, which reduced the N required to produce N 2 O.…”
mentioning
confidence: 99%